Total Bioactive Contents, Metabolic Profiling, Docking Studies, Antioxidant and Enzyme Inhibition Activities of Convolvulus Arvensis L. and Multivariate Analysis to Unravel a Potential Herb as Natural Resource for Pharmaceutical Industry. Issue 11 (17th October 2022) - Imran Tousif, Muhammad; Nazir, Mamona; Saleem, Muhammad; Tauseef, Saba; Uddin, Reaz; Zengin, Gokhan; Fawzi Mahomoodally, Mohamad; Abbas, Zaheer
Abstract: Convolvulus arvensis L. is an evergreen herb growing in various regions of Pakistan. Despite of several medicinal properties associated to this herb, it was not investigated scientifically for its bioactive compounds and detailed pharmaceutical properties. Therefore, its methanolic extract was divided into hexane (CA−H), chloroform (CA−C), ethyl acetate (CA−E) and butanol (CA−B) soluble fractions. CA−H and CA−C were found rich in phenolics (30.73±0.63 and 20.15±0.59 mg GAE/g of the extract, respectively), and the same fractions exhibited significant antioxidant activities (DPPH: 5.23±0.11 & 12.34±0.17 mg TE/g extract, respectively; ABTS: 36.82±0.04 & 56.74±0.61 mg TE/g extract, respectively). Also in CUPRAC activity assay, CA−H and CA−C exhibited highest activities as 87.30±0.46 and 56.74±0.61 mg TE/g extract, respectively, while CA−C was most active in FRAP activity assay with value of 40.21±2.19 mg TE/g extract. Total antioxidant capacity (1.23±0.033 mmol TE/g extract) was also found higher for CA−C, while CA−H activity was also comparable, however, CA−H showed higher metal chelating activity (22.74±0.001 mg EDTAE/g extract) than that of CA−C (17.55±0.22 mg EDTAE/g extract). These activities clearly revealed a direct relation between antioxidant potential and phenolic contents of CA−H and CA−C. In AChE and BChE inhibitory assay, CA−H and CA−E showed better inhibition (AChE: 8.24±0.77 & 4.46±0.007 mg GALAE/g extract; BChE: 5.40±0.02 & 1.92±0.24 mg GALAE/g extract) as compared to other fractions, whereas, against tyrosinase, CA−B was most active (37.35±0.53 mg KAE/g extract). CA−H and CA−C also showed higher inhibitory potential (0.98±0.08 & 0.58±0.01 mmol ACAE/g extract) against α‐Amylase; while against α‐Glucosidase, CA−E was the most active fraction. UHPLC/MS analysis of the methanolic extract of C. arvensis disclosed the presence of 62 compounds as sterols, triterpenes, flavonoids, fatty acids, alkaloids and coumarins. In Multivariate Analysis, the total phenolic contents were correlated strongly with all antioxidant assays except FRAP and DPPH. Regarding enzyme inhibitory properties, only AChE, BChE and α‐amylase were correlated with the total phenolic contents in the extracts. Docking analyses confirmed these findings, as identified compounds had high binding free energy and inhibition constants with the enzymes studied. It was finally concluded that C. arvensis is a potential industrial crop, which can be a component of nutraceuticals and functional foods, if evaluated for its toxicity. Abstract :